Sustainable supply network structure: understanding impact of interfirms’ relations as drivers of supply network complexity - Lokhman Hakim Osman,; Siti Norida Wahab,; Ahmad Raflis Che Omar,; Suraiya Ishak,; Azhar Ahmad, (Penerbit Universiti Kebangsaan Malaysia, 2020)
This study examined the Inter-Firm Relation (IFR) as one of the elements to enhance Sustainable Supply Network Structure (SSNS) management in Malaysian maritime industry supply network. IFR has been an interesting research area for academics and businesses practices due to its relevance in determining the best practices and impacts to encourage SSNS. The Social Network Analysis (SNA) method was adopted to develop valid attribute for the measurement process and the embeddedness theory was used to evaluate IFR among the proposed attributes. These methods enable the researcher to transform relational data in the form of network matrix and produce reliable results for theoretical and industrial applications which have not been discovered in previous studies. A total of 37 managers in a maritime industry supply network were approached to participate in this study. Result revealed that IFR has different effects on the formation of SSNS. The finding provides useful insight in formulating the importance of IFR towards improving and understanding SSNS, particularly, in the Malaysian maritime industry. The contribution of this research extends to the literature and put forward solutions for the industry since previous studies are neglecting IFR, which is highlighted as a source of supply network complexity.